Physico-chemical Properties of Lateritic Soil Treated with Limestone Powder and Fly-Ash (FULAFIA IAC Book of Proceedings, 2024)
The quality of embankment construction directly influences the performance of the supported infrastructure. This research examined the quality of lateritic soil stabilized with limestone powder (LS) and fly ash (FA) through changes in the physico-chemical properties of mixtures. The representative lateritic soil was treated with a predetermined optimum LS content of 6% and varying proportions of FA (3, 6, 9, 12 and 15% by dry weight of soil). Physico-chemical test such as Atterberg limits (Liquid and plastic limit), linear shrinkage, specific gravity, cation exchange capacity (CEC), electrical conductivity (EC) and pH were conducted on soil mixtures. The result of the tests revealed that the natural soil was classified as A-7-5 and MH (inorganic silts) under ASSHTO and USCS classification systems respectively. The study also found that the addition 6%LS to the natural soil increased the plasticity index to 24.4% from 17.2% for the natural soil, while the combined effect of 15%FA +6%LS decreased the value to 15.9%. Similarly, both specific gravity and linear shrinkage of mixtures containing LS and FA were found to be lower compared to that of the natural soil. On the contrary, pH of soil increased on introduction of 6%LS which increased further when FA was added due to their neutralizing and alkaline properties. Likewise, the combined treatment yielded higher CEC, indicating more exchangeable cations, while the EC increased with fly ash, suggesting increased dissolved ion concentration from fly ash's soluble salts.